Association of Toxoplasma Gondii Infection with Spontaneous Abortion (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: To evaluate whether there is any association of Toxoplasma gondii infection with spontaneous abortion.Materials and Methods: This observational case control study was conducted in the Department of Obstetrics and Gynaecology, Dhaka Medical College Hospital, Dhaka (DMCH), over a period of one year from 31st December 2008 to 30th November 2009. A total 91 pregnant women were selected for this study. Among them 46 patients of spontaneous abortion were selected as case and 45 healthy pregnant women were selected as control purposively. Spontaneous abortion cases were diagnosed on the basis of history, clinical examination and USG findings. Patients with medical disorder, Rh-incompatibility, multiple pregnancy, cervical incompetence, septic abortion, threatened abortion, fibroid with pregnancy and uterine anomaly were excluded from the study. The clinical examination was done by standard method. Blood was collected from each subject, serum was separated. Main outcome measure was presence of toxoplasma antibodies in spontaneous abortion cases. Antibody was detected by ELISA method. A p value of